Analisis Tingkat Pemahaman Masyarakat terhadap Sistem Pemasaran Syariah pada Asuransi PT Takaful Keluarga - Azizah Rahmah; Nuri Aslami (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
The ilevel iof iunderstanding iof ithe isharia iinsurance icommunity iis ivery iinfluential iin ithe imarketing iof isharia iinsurance iproducts. iThe ipurpose iof ithis ipaper iis ihow ithe ipublic's iunderstanding iof isharia iinsurance iand iwhat iobstacles iare ifaced iby isharia iinsurance icompanies iin imarketing itheir iproducts. iThis iresearch imethod iuses iqualitative iresearch iwhich iis isupported iby idata iand ianalysis iof istudies ithat ihave ibeen icarried iout iby iprevious iresearchers ias iwell ias isome iinformation ifrom ithe iinternet. iThe iresults iof ithis istudy iindicate ithat ithere iis ia ilack iof ipublic iunderstanding iof ithe iPT iTakaful ifamily imarketing isystem, itherefore isocialization ifrom ithe ifamily iTakaful iInsurance iand ithe iGovernment ineeds ito ibe iimproved iso ithat ipeople iknow imore iabout ithe icorrect isharia imarketing isystem iin iaccordance iwith ipractice iwithout iany iengineering. Keywords: sharia iinsurance, ilevel iof ipublic iunderstanding, isharia imarketing isystem